Bittersweet Metamorphosis: Lived Experiences of Emerging Adult Single Fathers on Parenting in a Rural Community - Arboleda, Daniel John D.; Singson , Deborah Natalia E. (Technium Social Sciences Journal, 2022)
With the increasing number of single-father family households worldwide, there is a need to conduct substantial research to provide sufficient information about this understudied population. This qualitative phenomenological study seeks to describe, explore and interpret the lived experiences of emerging adult single fathers on parenting. It utilized the purposive and snowballing sampling techniques to select the participants. The data were gathered through face-to-face interviews guided by interview protocol. Lichtman’s 3 C’s of Data Analysis was employed to generate themes extracted from participants’ verbatim transcripts. Five themes emerged from their lived experiences: Providing Care and Nurturance, Rearing One’s Child Properly, Dealing with Drawbacks in Single Fatherhood, Receiving Relief from Empathic Hands, and Appreciating Blissful Moments in Solitary Parenting. The findings provided insights that a transformation is required to adjust to their current situation and, most significantly, to change for their children’s sake. To conclude, single fathers can truly nurture and raise their children with tenderness, warmth, care, and affection like single mothers and dual-household families. Given the limitations of this qualitative research, quantitative research is suggested for further research to create a comprehensive intervention program for mental health professionals to promote single fathers’ quality of life.